Designing and Prototyping Record System for Machine Usage Time - Antonia Karima Yanti; Erwin Sitompul (Journal of Electrical And Electronics Engineering, 2019)
Machine cost is one of the components of production cost. Accurate record of machine usage time is thus crucial to obtain accurate production cost calculation. Besides, machine usage time can be used as parameter to assess the performance of the machine operator. Furthermore, the data can be used as input to the machine’s maintenance and reparation plan. The author is motivated by the current problems found at Akademi Teknik Mesin Industri (ATMI) Cikarang, where it is still possible to use one machine simultaneously by more than one operator. This causes inaccuracy in calculation of machine usage time and production cost. In this paper, the author proposed a design of device to record detailed data of shop drawing and machine usage time. By the use of this device, a certain machine will be activated and deactivated by using RFID technology, with the whole system controlled by Arduino Mega 2560 microcontroller. Furthermore, the shop drawing and machine usage time will be able to be accessed through a Windows-based interface application, implemented by using Visual Studio. A database is also made available by using Microsoft Access. The use of the proposed device makes possible of accurate measurement of production time efficiency and machine operator performance. Through this improved accuracy, further analysis can be made in order to achieve production improvements in planning, process, and maintenance.